2008
DOI: 10.1016/j.neubiorev.2007.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Multiple systems of category learning

Abstract: We review neuropsychological and neuroimaging evidence for the existence of three qualitatively different categorization systems. These categorization systems are themselves based on three distinct memory systems: working memory (WM), explicit long-term memory (explicit LTM), and implicit long-term memory (implicit LTM). We first contrast categorization based on WM with that based on explicit LTM, where the former typically involves applying rules to a test item and the latter involves determining the similari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 45 publications
(90 reference statements)
2
57
1
2
Order By: Relevance
“…Behavioural studies suggest potential problems with working memory, procedural memory and long-term memory. These systems are also referred to as short-term explicit memory, long-term implicit memory and long-term explicit memory (Smith & Grossman, 2008). There are still many views regarding the logical and neurological organisation of the memory system.…”
Section: Relations Between Sli and Advances In Neurological Researchmentioning
confidence: 99%
“…Behavioural studies suggest potential problems with working memory, procedural memory and long-term memory. These systems are also referred to as short-term explicit memory, long-term implicit memory and long-term explicit memory (Smith & Grossman, 2008). There are still many views regarding the logical and neurological organisation of the memory system.…”
Section: Relations Between Sli and Advances In Neurological Researchmentioning
confidence: 99%
“…On each trial, participants are presented with two cues: one an imperfect predictor I, and the other either a common perfect predictor PC or rare perfect predictor hidden to behavior. As a first pass, the goal of distinguishing between the neural regions associated with high-level inferential processes, such as hypothesis testing, rule switching, and problem solving and lower-level associative learning have been one of the main foci of neurobiological category learning research (Ashby and Maddox, 2005;Smith and Grossman, 2008;Seger and Miller, 2010). For example, rule-based processes, akin to those underlying inferential theories, are thought to depend upon cortico-striatal loops involving the PFC and head of the caudate nucleus, whereas simple visual associations may be learned using visual and procedural loops connecting the tail of the caudate with visual regions and motor outputs.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, learning scenarios such as information-integration category learning, (where there is a within-category interdependence among certain featuredimensions), or some prototype learning tasks, involve learning representations which people fail to describe verbally (Ashby and Gott, 1988). For this reason it is frequently suggested that learning different category structures involves a variety of computational challenges, which are met by different neural mechanisms in the human brain (Ashby and O'Brien, 2005;Smith and Grossman, 2008).…”
Section: Introductionmentioning
confidence: 99%